2018
DOI: 10.1371/journal.pone.0202483
|View full text |Cite
|
Sign up to set email alerts
|

3-year-data of combined navigated laser photocoagulation (Navilas) and intravitreal ranibizumab compared to ranibizumab monotherapy in DME patients

Abstract: PurposeThe prospective, comparative evaluation of combined navigated laser photocoagulation and intravitreal ranibizumab in the treatment of diabetic macular edema has shown advantage of a combination therapy compared to ranibizumab monotherapy at year 1 with significantly reduced injections. The purpose of this retrospective study was to determine the long-term visual gains and need of injections in a 3 year-follow-up period.MethodsRetrospective analysis of patients of the original study in the long-term foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
0
3
0
4
Order By: Relevance
“…In 3 years of treatment, the study demonstrated a similar improvement in best‐corrected visual acuity (BCVA) but with a lower need for additional intravitreal injections in the combination group (Herold et al. ). However, it is unknown whether the difference in results of combination therapy in DME treatment can be attributed to the choice of photocoagulation system.…”
Section: Introductionmentioning
confidence: 86%
“…In 3 years of treatment, the study demonstrated a similar improvement in best‐corrected visual acuity (BCVA) but with a lower need for additional intravitreal injections in the combination group (Herold et al. ). However, it is unknown whether the difference in results of combination therapy in DME treatment can be attributed to the choice of photocoagulation system.…”
Section: Introductionmentioning
confidence: 86%
“…Previously, clinical trials on intravitreal anti-VEGF agent monotherapy in patients with DME showed that the mean improvement in BCVA was 0.81 logMAR after 3 months of treatment [33], and 0.3-3.85 logMAR after 12 months of treatment [34][35][36]. Our analysis of IVC monotherapy showed a mean logMAR BCVA scale improvement in which the largest change (6.09 logMAR) occurred at 3 months after treatment among retrospective studies (n = 4), which was higher than that previously reported.…”
Section: Confidence Intervalmentioning
confidence: 99%
“…Deshalb wurde in aktuellen Studien zum Teil auch Computer-assistiertes navigiertes Lasern verwendet (▶ Abb. 3) [152,254]. Eine genauere Dokumentation und präzise Applikation wird so ermöglicht (OD-OS GmbH, Teltow, Deutschland) [134,255,256].…”
Section: 1-2 Ivom-therapie Mit Steroidenunclassified
“…Die kombinierte Gabe von 0,3 mg Ranibizumab ("treat and extend" mit OCT-abhängiger Steuerung der Intervalle) mit und ohne navigierte Laserapplikation in Abhängigkeit von der Netzhautdicke wurde mit einem dritten Arm (Ranibizumab mit fixer monatlicher Therapie) verglichen; über 2 Jahre unterschied sich die Anzahl der Ranibizumab-Injektionen in dem Kombinationsarm kaum (17,5 vs. 18,9) gegenüber dem Treat-and-Extend-Monotherapiearm [152]. Eine kleinere Studie mit Wiederbehandlung nach PRN-Schema hat dagegen eine Reduktion der IVOM-Anzahl durch additive Verwendung derselben Lasertechnologie berichtet: Während des ersten Jahres unterschied sich die Behandlungsfrequenz deutlich (0,88 ± 1,23 Kombi-vs. 3,88 ± 2,32 Ranibizumab-0,5-mg-Monotherapie), diese Tendenz setzte sich auch über die folgenden 2 Jahre (2,91 ± 2,3 Kombi-vs. 3,85 ± 3,7 Ranibizumab-0,5-mg-Monotherapie) fort [254].…”
Section: 1-2 Ivom-therapie Mit Steroidenunclassified